Piracy of optical discs: the effectiveness of copyright law in Malaysia / Azura Idayu ... [et al.] - Azura Idayu (2006)
The effectiveness of Copyright Law in curbing the piracy of optical discs has always been a debatable issue in our country. Due to the fact that piracy is an illegal activity, we hereby would like to raise the issue on the effectiveness of the copyright law in Malaysia. The main aim of this research is to see whether the law is effective enough in its process to curb the activity of these so called pirates. During the course of this study, several relevant and reliable sources will be referred to. These sources include legal material such as statutes, case laws, law reports and books. Other sources of information include newspapers, articles, internet sources, ideas and suggestions that arose from the interview that we have conducted. The interview was conducted to obtain perspectives on the legal aspects, problems of enforcement of law, current situation in the country, factors that contributed to the problem of piracy and also factors that influence people to buy pirated items. It is hoped that at the end of this study, a better understanding of the position of the law regarding the problem of piracy could be gained.